Uterine fibroids - a literature review - Pokora, Karolina; Pokora, Szymon; Podsiedlik, Adam; Stefanowicz, Agata; Poloczek, Alicja; Szczerba, Jakub; Jeleń, Katarzyna; Sojka, Paweł; Pokładnik, Dominika; Żymła, Tatiana (Journal of Education, Health and Sport, 2024)
Uterine fibroids are the most common benign neoplastic lesions occurring in women. They are formed as a result of proliferation of smooth muscle tissue cells. Their appearance and proliferation are influenced by both genetic and environmental factors. 70% of them remain asymptomatic, so they are often detected only during a routine gynecological examination or pelvic imaging studies. Uterine myomas can generate pelvic and lower abdominal discomfort and pain, abnormal, prolonged, heavy bleeding, anemia, dyspareunia, frequent urination, bloating, constipation, abdominal cramps, low back pain and obstetric complications. Available therapeutic strategies include conservative, pharmacological and surgical treatment. The choice of a particular method is considered on an individual basis and depends on the presence of clinical symptoms, the size, location of the myomas, or the age and procreative plans of the patient.